Membentuk Karakter Anak Melalui Pendidikan Pra Nikah - Taufiqurohman (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2021)
This paper discusses how to shape children's character through premarital education. In the family environment, parents are obliged to protect, educate, maintain, and guide and seriously direct the child's behavior or personality in accordance with Islamic law which is based on the guidance or rules that have been determined in the Koran. and hadith. This task is the responsibility of each parent that must be carried out. Of course, the education that is presented is like a chain of relationships that cannot be separated from the education of the parents themselves, so that if you are going to educate children, parents must also have the knowledge, in this case it can be prepared through pre-marital education. the author if you want to build a child's mental, it is necessary to foster and prepare a good family. Pre-marriage education as a problem solving is a concrete means and a way in the realm of the field through institutions, meaning that pre-marriage education is not only a formality at BP4 but pre-marital education can be carried out as long as the marriage runs, both by the community and the family itself.